Преобразуйте выражение в многочлен стандартного вида 1) 3a(2-b) 2) (5a-6b)(6b-5a) 3) (x-y)(x+y)(x-y)

asel07071 asel07071    1   14.09.2019 02:50    0

Ответы
sashashenko sashashenko  21.08.2020 07:55

1) 3a(2-b) = 3a×2 - 3a×b = 5a - 3ab

2) (5a-6b)(6b-5a)= 5a×6b+5a×(-5a) -6b×6b-6b×(-5a)=6b5a-25a-36b+6b5b

3)(x-y)(x+y)(x-y) = (x×x+x×y-y×x-y×y)(x-y)=(x²+xy-yx-y²)(x-y)=

x²×x+x²×(-y)+xy×x+xy×(-y) -yx×x-yx×(-y) -y²×x-y²×(-y)=

x³-x²y+x²y-xy²-yx²-y²x-y²x+y³

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра